Semiotic Analysis of Family Communication Behavior on Children's Mental Health In Films “Andai Ibu Tidak Menikah Dengan Ayah” - Kholifah Nur Jannah; Luthfira Aslinda; Deayu Attamimi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Family communication plays an important role in shaping children's mental health through various interactions that occur within the family environment. The film Andai Ibu Tidak Menikah dengan Ayah portrays various representations of family communication behaviors that influence children's psychological conditions. This study aims to analyze the meaning of family communication behaviors related to children's mental health as represented in the film Andai Ibu Tidak Menikah dengan Ayah. This research employs a descriptive qualitative method with Ferdinand de Saussure's semiotic approach. The research object consists of scenes, dialogues, expressions, and visual signs depicting communication interactions within the family. Data were collected through observation and documentation of scenes relevant to the research focus. Data analysis was conducted using Saussure's concepts of signifier and signified to reveal the meanings contained in the representation of family communication behaviors. The results show that the film represents various forms of family communication behavior through verbal and nonverbal signs. These behaviors include a lack of openness, family conflicts, emotional neglect, and limited psychological support for children. Such signs represent children's mental health conditions characterized by feelings of loneliness, anxiety, insecurity, and difficulties in expressing emotions. On the other hand, several scenes also highlight the importance of empathy, attention, and emotional support in fostering better mental health among children. Through Ferdinand de Saussure's semiotic analysis, the film demonstrates that family communication behaviors serve as symbols representing the close relationship between family dynamics and children's mental health. This study concludes that Andai Ibu Tidak Menikah dengan Ayah illustrates the importance of healthy family communication as a foundation for children's psychological development and mental well-being.